The difficult diagnosis of floor of the mouth masses: a case report - Alexe De Ferm; Bart Van Boven; Maaike Cornelis; Rafael Jacobs (The Egyptian Journal of Otolaryngology)
Abstract Background Lymphatic malformations can present as a floor of the mouth mass, they are rare vascular lesions, presenting most frequently in the head and neck region and mostly presenting at birth or before 2 years of age. Clinical and diagnostic findings can make the differential diagnosis with other floor of the mouth masses, such as ranulas, difficult. Case presentation We present a case of a 7-year-old girl with a sudden swelling in the floor of the mouth without infectious characteristics. Clinically and after imaging, the swelling was most compatible with a ranula. After sublingual sialadenectomy, recurrence of the swelling occurred. Multiple evacuating punctures were needed for symptomatic relief. Given the clinical evolution and new imaging, diagnosis of a lymphatic malformation became more likely. Sclerotherapy was performed with size stabilization. Conclusion Floor of the mouth masses comprise a group of different pathologies with different presentations, diagnostic findings and treatment. Differential diagnosis can be challenging. This case report presents an overview of the presentation and management of floor of the mouth masses, focused on lymphatic malformations, with characteristics distinguishing them from other pathologies such as ranulas.